Consumer behavior in sports marketing in the context of football - Khudiyev, Murad; Szabó, Zoltán (Studia Mundi – Economica, 2020)
This article evaluates the main concepts of Sports Marketing that influences on consumer behavior in the context of football. As it is disputable if sports consumers are unique or not, within researchers and marketers, this article also tries to investigate the literature presenting opinions on the topic. The author has tried to find out the main traits that make sports consumers unique or non-unique by synthesizing academic literature and a case study on Fenerbahce SK. This research is not empirical and presents a theoretical framework.
Keywords: Sports Marketing; Football Marketing; consumer behavior; commitment; uniqueness